Hematopoietic Cell Transplantation in Children with Cancer - Smith, Franklin O.; Smith, Franklin O.; Reaman, Gregory H.; Reaman, Gregory H.; Racadio, Judy M.; Racadio, Judy M. (Pediatric Oncology,, 2014)
This book is a comprehensive and up-to-date compendium on all aspects of blood and marrow transplantation in children. After an introductory chapter describing the history of pediatric blood and marrow transplantation, subsequent chapters discuss pediatric-specific aspects of transplantation, including stem cell sources suitable for transplantation, preparative regimens, graft-versus-host disease, complications related to transplantation, and late effects. The role of blood and marrow transplantation in various specific pediatric diseases is then examined, and the closing chapter considers future directions. The book is co-authored by experts in the treatment of pediatric malignant and non-malignant diseases that are potentially treatable with blood and marrow transplantation and by specialists in the practice of transplantation medicine. All of the authors are internationally recognized authorities and they offer a largely evidence-based consensus on etiology, biology, and treatment. This handbook has far-reaching applicability to the clinical diagnosis and management of pediatric diseases that are treatable with blood and marrow transplantation and will prove invaluable to specialists, generalists, and trainees alike.   .